Religiusitas dan entrepreneurship - Muhammad Shohib (Cognicia, 2020)
Entrepreneurship has contributed considerably in the country'seconomic growth, so research on this theme is increasingly in demand andgrowing well. Religiosity has given a distinctness in the individual andinfluenced his behavior. This study aims to examine the relationship of religiositywith entrepreneurship by using literature review. Literature review search wascunducted on ProQuest, EBSCO, Science Direct electronic database usingkeywords of entrepreneurship and religiousity. We found that religiosity has astrong association with entrepreneurial behaviors and traits, both as a distinctivefeature of entrepreneurial character that distinguishes between high and lowreligiosity, strategy in entrepreneurship and other psychological aspects ofentrepreneurship.